Encyclopedia of social and cultural anthropology - Barnard, Alan (Alan J.); Spencer, Jonathan 1954- (London Routledge, 1996)
This volume provides a unique guide to the ideas and history the ideas and history of the discipline which discusses human, social and cultural life in all its diversity. Theory, ethnography and history are combined in over 200 substantial entries on topics as wide ranging as race, postmodernism, witchcraft, essentialism, magic and methodology. Authoritative entries have been commissioned from among the world's leading specialists. Alphabetically organized, the main entries contain clear, concise and provocative explanations of key anthropological themes and ideas, as well as surveys of the most important regional traditions of ethnographic research. Each entry contains cross references and a bibliographic guide to further reading. The Encyclopedia also contains a biographic appendix, with details of the lives and works of over 200 important figures in the history of anthropology and a glossary with short explanations of over 500 terms and concepts. Areas covered include: History of anthropological research, colonialism, orientalism and occidentalism, theories of culture and society * Kinship, gender and family, marriage, the body * Ritual and religion, language and linguistics, poetics, literacy, aesthetics, film, museums * Relations with other disciplines (e.g. archaeology and sociology).
Includes Biographical appendix (pages [568]-593).
Includes bibliographical references and indexes.
Keywords: Ethnology -- Encyclopedias; Etnologia -- Encyclopedias